STRATEGI PARENTING DALAM MEMBENTUK KESEJAHTERAAN PSIKOLOGI ANAK MENUJU KOTA SURABAYA SEHAT SEJAHTERA - Alifatul Reniwati Zumroh; Amirul Mustofa (Halu Oleo University, 2024)
The purpose of the study is to analyze the effectiveness of the parenting program strategy implemented by the Surabaya City Government in improving children's psychological well-being. This strategy seeks to create a healthy and prosperous city of Surabaya through good parenting, nutritional fulfilment, and adequate health facilities for children. The research method uses a mixed method combining qualitative and quantitative methods with data collection through interviews and questionnaires. The results of the study show that the Great Parents School (SOTH) Program provides an ideal platform for parents, especially mothers, to learn and seek knowledge about good parenting. The SOTH program provides significant benefits to mothers by providing effective parenting education, helping them cope with emotional challenges, teaching children to socialize, and practising language skills. The program is expected to be implemented in various regions to support child development and better parenting.